Operation principle analysis of multi-function SF6 insulating gas decomposition product field detector. Issue 1 (March 2021) - Zhang, Jiguo; Xu, Yi; Peng, Bo; Ma, Yao; Wang, Yu; Zhao, Jinyu; Lin, Xin; Chen, Jingzhe
Abstract: In recent years, SF6 gas insulated equipment is widely used in power system to meet the development needs of power industry. The change of CF4 content is of great significance for analyzing the insulation state of electrical equipment. In this paper, a new technology and equipment for on-site detection of CF4 in SF6 gas based on spectral absorption principle is studied. It provides reference and technical support for the operation and maintenance of SF6 gas insulated equipment and the condition based maintenance of equipment in the future.